Analysis of the Validity and Readability of Google Sites Learning Media with a STEM Approach on Mutation Material to Improve Student Critical Thinking Skills - Nurussalma, Syafina; Yuniastuti, Ari; Mustikaningtyas, Dewi; Parmin, Parmin (Universitas Negeri Semarang, 2024)
The use of technology is currently relevant to the implementation of the ‘Merdeka Belajar’ Curriculum, but has an impact on students' critical thinking skills and learning media needs. This means that educators need to provide innovation in learning that is linked to technology. This study purpose to analyze the validity and readability of Google Sites learning media with a STEM approach to mutation material. This study used research and development (R&D) methods but was limited to the implementation stage, namely small-scale testing. A small-scale trial was carried out on 20 students of class XII MIPA 2 at Gemuh 1 Senior High School. The instruments used in this study were validation sheets and media readability questionnaires. Product validity criteria are seen from the validator's assessment. Criteria for media readability are seen from the results of student questionnaires. The study results show that the validity of the media was declared very valid based on the assessment of media experts at 96% and material experts at 93.56%. The media readability value was declared very good based on student assessments of 88.64%, so it has the potential to improve high school students' critical thinking skills.